Associative and Gender Aspects of the Emotional Concept of Jealousy in the Ukrainian Linguistic Culture - Petiak, Olena (East European journal of psycholinguistics, 2020)
The article deals with the associative and gender features of the perception by marriage partners of the emotional concept of "jealousy" within the framework of Ukrainian linguistic culture. Associative and gender features of the emotional concept of “jealousy” were found out as a result of data analysis of free word association test held with 100 Ukrainian speaking students, graduate students, and teachers (50 men and 50 women) at Khmelnytskyi National University (Ukraine). The respondents were in official marriage; their age was from 18 to 65. With the help of the free word association test the connections of the concept of "jealousy" in the Ukrainian language consciousness and the semantic zones of this stimulus word were determined. An important step was to take into account the opinions of the researchers regarding the possible difference between manifestations and the emergence of jealousy in men and women. It has been established that the understanding of jealousy by marriage partners occurs through an appeal to color perception. Psycholinguistic ideas about jealousy are manifested in the ambivalence of emotions, the semantic signs of which are the polar properties of “love” (“care”) – “hatred” (“doubt”, “suspicion”). The gender factor affects the structure of the associative field of the concept of "jealousy" and determines both the quantitative indicators in the structure of the organization of the associative field of the concept, as well as its “semantic content”. Qualitative analysis of the results of the free association test helped to form separate fragments of male and female world images in their linguistic consciousness and made it possible to talk about gender stereotypes regarding jealousy in the everyday linguistic consciousness of marriage partners. References Гаврилів О. Непряма вербальна агресія. East European Journal of Psycholinguistics. 2019. Т. 6, № 2. С. 7–20. Изард К. Э. Психология эмоций. Нижний Новгород: Питер, 2002. Ильин Е. П. Эмоции и чувства. C.-Петербург: Питер, 2016. Карзенкова Е. П. Дискурс близких взаимоотношений (как он есть). Проблемы социо- и психолингвистики: Динамика языковых ситуаций. Пермь: Изд-во Перм. ун-та, 2006. С. 181-188. Карзенкова Е. П. Дискурс близких взаимоотношений: любовь как стихия. Проблемы социо- и психолингвистики. Пермь: Изд-во Перм. ун-та, 2006. С. 165-173. Кубрякова Е. С. Начальные этапы становления когнитивизма: лингвистика – психология – когнитивная наука. Вопросы языкознания, 1995. № 4. С. 3-15. Маслоу А. Мотивация и личность. Москва: Питер, 2008 . Мень А. Мировая духовная культура. Нижний. Новгород: Нижегородская ярмарка, 1995. Рубинштейн С. Л. Основы общей психологии. Санкт-Петербург: Питер, 2006. Спиноза Б. О происхождении и природе аффектов. Психология эмоций /под ред. В. К. Вилюнаса, Ю. Б. Гиппенрейтер. Москва: Изд-во Моск. ун-та, 2008. C. 50-62 Стернин И. А. Понятие коммуникативного поведения и проблемы его исследования. Русское и финское коммуникативное поведение. Воронеж: Изд-во ВГТУ, 2003. C. 4-20. Фромм Э. Состояние человека. Москва: Смысл, 1995. Фуко М. Історія сексуальності. Харків : Око, 2000. Хомуленко Т., Кузнецов А. Психолингвистическое значение концепта «вера». Psycholinguistics-Psiholingvistika. 2019. Вип. 25, № 1. С.  338-362. Шевцов А., & Гупаловська В. Психосемантичний зміст поняття сексуальності в мовній свідомості дорослих. Psycholinguistics-Psiholingvistika, 2020, Вип. 27, № 1. С. 310-334. https://doi.org/10.31470/ 2309-1797-2020-27-1-310-334. Юшкова Н. А. Концепт «ревность» в художественной картине мира Ф. М. Достоевского. Житниковские чтения: Межкультурная коммуникация в когнитивном аспекте. Челябинск, 2001, 198-199. Pines A. (1992). Romantic Jealousy: Understanding and Conquering the Shadow of Love. New York: St. Martin’s Press. Kristjansson K. (2002). Justifying Emotions: Pride and Jealousy. L.: Routledge. Lyubimova, S. (2017). Etymological memory of a word in designating sociocultural stereotype. East European Journal of Psycholinguistics, 4(1), 140-149. Terekhova, D. (2018). An experimental study of the lingual consciousness of Ukrainians and Russians (Dynamic aspect). East European Journal of Psycholinguistics, 5(1), 92-110. References (translated and transliterated) Havryliv, O. (2019). Nepriama verbalna agressiya [Indirect verbal aaggression]. East European Journal of Psycholinguistics, 6(2), 7–20. Izard, K. E. (2002). Psikhologiya Emotsii [Psychology of Emotions]. Nizhny Novgorod: Piter, 446. Ilyin, E. P. (2016). Emotsii i Chuvstva [Emotions and Feelings]. S.-Petersburg: Piter. Karzenkova, E. P. (2006). Diskurs blizkikh vzaimootnoshenii (kak on yest) [Discourse of intimate relationships (as it is)]. Problems of Socio- and Psycholinguistics: Dynamics of Linguistic Situations, 181-188. Karzenkova, E. P. (2006). Diskurs blizkikh vzaimootnoshenii: lyobov kak stikhiya [Discourse of intimate relationships: love as the element]. Problems of Socio- and Psycholinguistics, 165-173. Kubryakova, E. S. (1995). The initial stages of the formation of cognitivism: linguistics-psychology-cognitive science. Voprosy Linguistiki, 4, 3-15. Maslow, A. (2008). Motivatsiya i Lichnost [Motivation and Personality]. Moscow: Piter. Men, A. (1995). Mirivaya Dukhovnaya Kultura [World Spiritual Culture]. Nizhny Novgorod: Nizhegorodskaya Yarmarka. Rubinstein, S. L. (2006). Osnovy Obshchey Psikhologii [Fundamentals of General Psychology]. St. Petersburg: Peter, 720. Spinoza, B. (2008). O proiskhozhdenii i prirode affectov [On the origin and nature of affects]. Psychology of Emotions. (pp. 50-62). V. Viliunas, Y. Gippenreiter, (Eds.). Moscow: Moscow University. Sternin, I. A. (2003). Poniatiye kommunikativnogo povedeniya i problem yego issledovaniya  [The concept of communicative behavior and the problems of its research]. Russian and Finnish Communicative Behavior. (pp. 4-20). Voronezh: Voronezh University Publishing House. Fromm, E. (1995). Sostoyaniye Cheloveka [The Human Condition]. Moscow: Sense. Foucault, M. (2000). Istoriya Sexualnosti [The History of Sexuality]. Kharkiv: Oko. Khomulenko, T., Kuznetsov, A. (2019). Psycholinguistic meaning of the concept of “Faith”. Psycholinguistics-Psiholingvistika, 25(1), 338-362. https://doi.org/10.31470/2309-1797-2019-25-1-338-362 Shevtsov, A., & Hupalovska, V. (2020). Psychosemantic content of the concept of sexuality in the linguistic consciousness of adults. Psycholinguistics-Psiholingvistika, 27(1), 310-334. https://doi.org/10.31470/2309-1797-2020-27-1-310-334 Yushkova, N. A. (2001). Kontsept “Revnost” v khudozhestvennoy kartine F. M. Dostoevskogo [The concept of “jealousy” in the F. M. Dostoevky’s artistic world image]. Zhitnikovsky Readings: Intercultural Communication in the Cognitive Aspect, 198-199. Pines, A. (1992). Romantic Jealousy: Understanding and Conquering the shadow of love. New York: St. Martin's Press. Kristjansson, K. (2002). Justifying Emotions: Pride and Jealousy. L.: Routledge. Lyubimova, S. (2017). Etymological Memory of a Word in Designating Sociocultural Stereotype. East European Journal of Psycholinguistics, 4(1), 140-149.  https://doi.org/10.5281/zenodo.821718. Terekhova, D. (2018). An Experimental Study of the Lingual Consciousness of Ukrainians and Russians (Dynamic Aspect). East European Journal of Psycholinguistics, 5(1), 92-110. https://doi.org/10.5281/zenodo.1436306.